A new mechanism for autophagy regulation of anti-tumor immune responses - Thorburn, Andrew (Autophagy, 2020)
In this commentary I discuss a recent paper that describes a new mechanism for how macroautophagy/autophagy regulates the immune response to cancer, and relate it to other recent studies in this area. These recent developments may allow more effective strategies to manipulate autophagy to improve cancer therapy.